The Impact Of Compensation And Leadership On The Organizational Commitment And The Implication On Employee's Turnover Intention Of Pt Provices Indonesia Central Office - Nurfadilah, Nadia (Universitas Mercu Buana, 2018)
The purpose of this study is to understand and describe the impact of compensation and leadership on the organizational commitment and its implications on turnover intention of the main office employees at the PT Provices Indonesia. There are 52 respondents (the whole employees). Data collection was conducted by interview and questionnaire. Path analysis (by using smartPLS3.0) and matric correlation analysis (by using SPSS24) among the variable dimensions were applied.The study revealed that: (1) compensation and transformational leadership have no significant impact on the organizational commitment, but has a significant impact on the Turnover Intention; (2) organizational commitment has no significant impact on the turnover intention; (3) It is not proved that organizational commitment is the mediator variable of the impact of compensation and transformational leadership on turnover. Based on the analysis of matric correlation among dimensions, to decrease turnover Intention, it is suggested to maintain and improve the following dimensions, such as; (1) indirect compensation versus planning to seek in other job; (2) transformational leadership planning to seek other job. Besides, to decrease turnover Intention: (1), the management suggests to redesign compensation, (2) doing leadership training, coaching and counseling. It is needed to ensure the convenient or comfortable environment) to do the job.